Enhanced production of functional extracellular single chain variable fragment against HIV-1 matrix protein from escherichia coli by sequential simplex optimization - Intachai,K. (Taylor and Francis Ltd., 2015)
The optimal culture condition for extracellular recombinant single chain variable fragment anti HIV-1 p17 protein (scFv anti-p17) production in Escherichia coli HB2151 was investigated by the sequential simplex optimization (SS) method. Five variable parameters were submitted in the fermentation process. The most favorable condition obtained from 19 independent experiments was as followed: 58 M of IPTG induction to 1.7 OD600 nm at 25.5°C for 16 h with 202 rpm agitation rate. The amount of secreted scFv anti-p17 at the optimal condition was 38% higher than under the control condition. The binding activity of soluble extracellular scFv anti-p17 protein increased 95.5% and 73.2% in comparison with the control condition and non-optimized condition respectively. The soluble scFv anti-p17 from crude HB2151 lysated was subsequently purified by immobilized metal ion affinity chromatography (IMAC) with His-tag. The purified scFv anti-p17 was intact and retained its antigen-binding affinity against HIV-1 p17. We demonstrated that the sequential simplex optimization method was a key for exertion of high yield with fewer experimental requirements for acquiring of large scale secretory protein production. © 2015 Taylor and Francis Group, LLC.